Climate risks reporting practices and assurance - Habib, Ahsan; Ehalaiye, Dimu; Islam, Ainul; Musundwa, Sedzani (Emerald Publishing Limited, 2025)
This volume contains an Open Access Chapter In recent years, the global business landscape has witnessed an increasing emphasis on sustainability and Environmental, Social, and Governance (ESG) considerations. This trend has led governments around the world to adopt policies aimed at addressing emerging ESG-related issues, including but not limited to climate-related risks. Climate Risks Reporting Practices and Assurance captures novel insights into the existing landscape of climate risk reporting practices and assurance practices related to Sustainability and ESG. Chapter authors discuss disclosure practices, climate risk assurance in New Zealand, responsible governance in sub-Saharan Africa, research opportunities within Science Based Targets, and valuation, accounting and climate risk. The Advances in Environmental Accounting & Management series aims to advance knowledge of the governance and management of corporate environmental impacts and the accounting involved.
Includes index.
Keywords: Climatic changes -- Risk assessment.; International business enterprises -- Environmental aspects.; Business & Economics -- Finance -- Financial Risk Management.; Finance and the finance industry.; Risk assessment.; elektronické knihy; electronic books